MODIFIKASI APROKSIMASI TAYLOR DAN PENERAPANNYA - Irpan Riski Munte; Imran M.; Musraini M. (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
We discuss a modified Taylor approximation for functions with periodic behaviour, which is a review of article of Martin et. al published on [Journal of Computational and Applied Mathematics, 130 (2001), 91–97]. This modification is based on the work of Scheifele in obtaining a solution of a perturbed oscillator.